A novel approach to studying transport in plasmas with magnetic islands. (24th July 2018) - Auriemma, F.; López-Bruna, D.; Lorenzini, R.; Momo, B.; Predebon, I.; Suzuki, Y.; López-Fraguas, A.; Narushima, Y.; Sattin, F.; Terranova, D.; Zhang, Y.
Abstract: In magnetically confined experiments the presence of rational surfaces modifies the magnetic configuration with one or more islands embedded in the main plasma. The islands strongly modify particle and heat fluxes, hence their role must be included in the study of the transport properties. Two examples of this phenomenology are here presented: a cold pulse propagation in LHD with an RMP (1, 1) island highlights a diffusivity reduction inside the island. A second study has been carried out on the RFX-mod reversed field pinch device where the transport on the ITB associated to a spontaneous m = 1 magnetic structure is discussed. To perform these studies a new approach in modeling transport in the presence of islands is presented: this new method, dubbed the multiple domains scheme (MDS), with some simplifying assumptions, is directly applicable to 1.5D transport codes. In the MDS different regions are identified inside the plasma all interfaced by the separatrix that acts as common boundary. In each domain a monotonic radial coordinate can be chosen and the metric elements can be computed accordingly. This scheme is independent of the equilibrium magnetic configuration hence it can be applied to either tokamaks, stellarators or reversed field pinches. The MDS has been implemented in a new numerical tool, dubbed the multiple axis solver.